„Wielkie uproszczenie” i „dryfujące sacrum”. „Angel-A” Luca Bessona jako popkulturowy apokryf - Jazownik, Monika (Załącznik Kulturoznawczy, 2023)
Apocrypha as testimony of non-canonical reading of sacred texts can provide a starting point for a discussion on works of popular culture. Luc Besson’s film Angel-A, as a kind of synecdoche of filmmaking about angels illustrates in a vivid, pop-culture way the trends of understanding and describing reality. The director’s portrait of the angel, much different from that proposed by the Bible, promotes a model of the world which provides a sense of freedom and lightness. In the end, however, does pop-culture have the power to release us from the weight of secrecy? It seems that everyone must experience that for themselves…